The Influence of Brand Experience and Perception Quality on Brand Loyalty Mediated by Brand Trust (Empirical Study: Mixue Consumers in Jakarta) - Gabriela Angeline (Asian Journal of Social and Humanities, 2023)
The purpose of this study was to analyze the effect of brand experience and perceived quality on brand loyalty mediated by brand trust (Empirical Study: Mixed Consumers in Jakarta). This research is a type of quantitative research by collecting data from 127 respondents using a questionnaire distributed online with a Likert scale. Data analysis using PLS-SEM with SmartPLS 3.0 software. The research results obtained from this study are brand experience has a significant effect on brand loyalty. Other results prove that perceived quality has a significant effect on brand loyalty, brand experience has a significant effect on brand trust, perceived quality has a significant effect on brand trust and brand trust has a significant effect on brand loyalty.